Intake, digestibility and nitrogen retention in goats fed ensiled maize stover and supplemented with snake bean (Bobgunnia madagascariensis) pod meal (Journal of Advanced Veterinary and Animal Research, 2017)
Objective: The aim of this study was to assess nutrient intake, digestibility and nitrogen (N) retention in goats fed ensiled maize stover (EMS) when supplemented with snake bean (Bobgunnia madascariensis) pod meal (BMM).Materials and methods: Eight local goats (21±2 Kg) in individual metabolic cages were divided into two groups. One group received a 100 gm BMM daily supplement to basal diet (EMS+50 gm maize bran), while the other group did not receive any supplement. The experimental design was a 2x2 switchback with 7 days of adaptation and 5 days of sampling of orts, feces and urine. Feed intake was recorded and total fecal collection was done to analyze digestibility of dry matter (DM), crude protein (CP), acid detergent fiber (ADF) and neutral detergent fiber (NDF), as well as N balance.Results: Goats receiving BMM supplement had higher (P